INOVASI PELAYANAN RUMAH JOGLO PEMILU PADA KPU PROVINSI JAWA TENGAH - Abid Irfan Nuhaa; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Public service is the main task of the government as a servant of the state and public servant. The government is required to improve the quality of service to be more effective and efficient so as to create excellent service. Innovation is indispensable in the development of a public service. One of the innovations applied by the Central Java Provincial KPU is the Rumah Joglo Pemilu. However, in the implementation of Rumah Joglo Pemilu has not run optimally. This study aims to analyze the characteristics of Rumah Joglo Pemilu innovation and analyze the factors driving and inhibiting innovation Rumah Joglo Pemilu. This research uses qualitative descriptive method research. The results showed that there are 5 characteristics of innovation in Rumah Joglo Pemilu that is retative advantage, compability, complexity, triability and observability. But on the characteristics of relative advantage and complexity can not be fulfilled. The driving factors in the innovation characteristic of Rumah Joglo Pemilu include room fittings, effectiveness, efficiency, and accountability, those who assist the development process, initiation to socialize Rumah Joglo Pemilu, and voter education become centralized. While the inhibiting factors include limited room size, limited costs, the scope of provision of data of electoral event, the establishment of Rumah Joglo Pemilu on the assets of the Central Java Provincial Government, the society has not been so friendly with a museum, has not had 4 requirements in the reform effort, measure success. Suggestions to be given include extending space, budgeting independently, coordinating, coordinating with the Provincial Government of Central Java related to building permits, socialization to the general public, need to initiate the training and research of Rumah Joglo Pemilu, and must establish indicators of success.